Development of United Kingdom Teaching Materials Containing Local Wisdom for Islamic University Students - Budiasih, Budiasih; Dewi, Fitri Ana Ika (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
This research aims to develop United Kingdom language teaching materials integrating local wisdom for Islamic higher education students. Local wisdom encompasses cultural values and knowledge internalized by students daily, hoping to increase their relevance and involvement in the learning process. The method used in this study is the Jolly and Bolitho development model, which involves the stages of needs analysis, planning, development, and evaluation of teaching materials. The results of this research are United Kingdom teaching materials specifically designed to meet the needs of students at Islamic universities, focusing on texts and content rooted in local wisdom. The development process faced several obstacles, including difficulties obtaining local knowledge-based texts, adjusting content to suit student needs, designing flexible learning plans, and time constraints. Experts validate and apply the teaching materials developed. The conclusion shows that integrating local wisdom in United Kingdom teaching materials makes learning more relevant and interesting for students and contributes to the preservation of local culture. Using culture-based learning resources allows students to learn language and cultural concepts in an integrated manner, which can ultimately increase their understanding and appreciation of local values in a global context.